Do voters discount political scandals over time? - Pereira, Miguel M.; Waterbury, Nicholas W. (Political Reserach Quarterly)
This paper explores how political scandals are discounted over time. Previous research has shown that voters respond disproportionately to recent economic conditions when evaluating incumbents. We argue that voters discount not only the performance of incumbents in office but also information about their personal character, largely due to accessibility biases. Building on a comprehensive database of congressional scandals covering the last four decades, we show that the electoral consequences of political scandals fade fairly quickly. Only cases emerging in the election-year systematically affect the vote share of incumbents. Moral scandals are the exception, with negative effects persisting over the entire term. In line with the mechanism proposed, additional analyses suggest this pattern results from disproportional levels of media attention, making moral scandals more easily retrieved from memory. The results broaden our understanding of the nature of myopic voting and provide an explanation for the increasing reliance on negative campaigning. - Reproduced.
Keywords: Voters, Democracy